Pengaruh Penggunaan Model Pembelajaran Role Playing Terhadap Peningkatan Kemampuan Bercerita Tentang Cerita Fantasi Siswa Kelas VII SMP Negeri 2 Iborongborong Tahun - Leben Panggabean; Berliana Simanjuntak (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to find out the influence of the role playing learning model on increasing the ability to tell fantasy stories about class VII students at SMP Negeri 2 Siborongborong for the 2022/2023 academic year. The population in this study was 252 students. The sample in this study was 34 students for the experimental group and 32 students for the control group. So the sample in this study was 66 students taken using a random technique. The instruments used to collect data are treatment or practice instruments. The method used in this research is an experimental method with a posttest only design research design. Hypothesis testing is carried out using the